The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1111/mcn.13391
|View full text |Cite
|
Sign up to set email alerts
|

Anaemia in Indians aged 10–19 years: Prevalence, burden and associated factors at national and regional levels

Abstract: Anaemia control programmes in India are hampered by a lack of representative evidence on anaemia prevalence, burden and associated factors for adolescents. The aim of this study was to: (1) describe the national and subnational prevalence, severity and burden of anaemia among Indian adolescents; (2) examine factors associated with anaemia at national and regional levels. Data (n = 14,673 individuals aged 10-19 years) were from India's Comprehensive National Nutrition Survey (CNNS, 2016(CNNS, -2018. CNNS used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 66 publications
1
9
0
Order By: Relevance
“…Besides socioeconomic factors, we have also examined the role of perceived hand hygiene behaviour and dietary diversity in nutritional outcomes. The study has found that stunting (29⋅9 %) and anaemia (39⋅6 %) are more prevalent among females ( 16 ) . Females are relatively more disadvantaged (2⋅23 times) in terms of anaemia compared with stunting.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Besides socioeconomic factors, we have also examined the role of perceived hand hygiene behaviour and dietary diversity in nutritional outcomes. The study has found that stunting (29⋅9 %) and anaemia (39⋅6 %) are more prevalent among females ( 16 ) . Females are relatively more disadvantaged (2⋅23 times) in terms of anaemia compared with stunting.…”
Section: Discussionmentioning
confidence: 96%
“…But due to lack of comprehensive and representative data on adolescent nutrition, the scope of earlier studies is a limited to specific region or gender ( 8 , 9 , 13 , 14 ) . Two recent studies on adolescent malnutrition ( 15 ) and anaemia ( 16 ) conducted using CNNS (2016–18) data shows substantial socioeconomic and regional disparities in adolescent malnutrition. However, none of these large-scale studies assessed the roles of dietary diversity and individual-level hygiene practices in adolescent malnutrition.…”
Section: Introductionmentioning
confidence: 99%
“…Because our results showed a decrease in serum zinc concentration following cancer treatment, we predicted that factors associated with post-treatment nutritional status as well as other factors may have contributed to reducing serum zinc concentrations. Therefore, we considered chemotherapy and radiotherapy, which result in decreased dietary intake, as possible factors associated with zinc deficiency; moreover, factors such as anemia ( 25 ) and hypoalbuminemia ( 26 ), which are indicators of malnutrition and are correlated with zinc concentrations, were considered. However, we observed that only cancer recurrence was associated with zinc deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…To develop solutions for addressing anaemia in India, a country with large subnational variations in diets and living conditions, it is important to understand if factors associated with anaemia vary across geographies. 19 The present study is aimed to determine the prevalence of anemia and its association with other determinants among adolescent girls (aged 10 to 19 years) in rural Varanasi of Uttar Pradesh. The outcomes of the study can be helpful for formulating effective interventions to prevent occurrence of anemia and its consequences among adolescent girls.…”
Section: Introductionmentioning
confidence: 99%
“…10 Existing studies on factors associated with anaemia in India mostly focus on women of reproductive age and children although there are some small studies on adolescents. [12][13][14][15][16][17] Studies conducted on anaemia among the adolescent girls (10)(11)(12)(13)(14)(15)(16)(17)(18)(19) years are not only few but also did not address societal determinants and the impact of these factors on anaemia prevalence.…”
Section: Introductionmentioning
confidence: 99%